Present and future of curricular materials - Díaz Pardo, Felipe (Avances en Supervisión Educativa, 2007)
Curricular materials constitute one of the essential components in a teaching schedule and must be understood as a helpful tool to facilitate the learning process developed in schools.Relevant regulations in force up to now assign text-books an outstanding importance as well as a self-sufficient category, and therefore subject to it the rest of materials, the so-called supporting material, which is regarded as complementary.Without the aim of diminishing the importance of text-books, present-day society would need a thorough reflection on the subject, taking into consideration the increasingly importance of new technologies, the appearance of new contents in official curricula and the new profile of students, with a variety of needs and interests, which provoke a diversity of educational programmes and services.